2013
DOI: 10.1016/j.cyto.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling of young overweight and obese female African American adults with prediabetes

Abstract: Approximately 5–10% of subjects with prediabetes become diabetic every year. Inflammation is involved in the development of obesity-related type 2 diabetes (T2D). However, to date, the relationship between inflammation and prediabetes, defined by hemoglobin A1c (HbA1c) ≥ 5.7 and < 6.5%, remains largely unexplored, especially in African Americans. Therefore, in this study we examined a comprehensive panel of 13 cytokines involved in the inflammatory response in overweight/obese subjects with prediabetes. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 58 publications
6
50
1
1
Order By: Relevance
“…To this regard, it is important to take into account that DM and prediabetes are considered pro-inflammatory states (Lucas et al, 2013;Nwose et al, 2014) that could be favoring the onset of ED by oxidative stress and by impaired regulation of calcium metabolism (Haubner et al, 2007;Patel et al, 2013;Piarulli et al, 2013;Tousoulis et al, 2013). An interesting but scarcely studied mechanism, probably associated with the onset of ED in the prediabetic patient, could be linked to toll like-receptors.…”
Section: Toll Like-receptorsmentioning
confidence: 97%
See 2 more Smart Citations
“…To this regard, it is important to take into account that DM and prediabetes are considered pro-inflammatory states (Lucas et al, 2013;Nwose et al, 2014) that could be favoring the onset of ED by oxidative stress and by impaired regulation of calcium metabolism (Haubner et al, 2007;Patel et al, 2013;Piarulli et al, 2013;Tousoulis et al, 2013). An interesting but scarcely studied mechanism, probably associated with the onset of ED in the prediabetic patient, could be linked to toll like-receptors.…”
Section: Toll Like-receptorsmentioning
confidence: 97%
“…Interestingly, the levels of these same markers were associated with the glucose levels in the prediabetic patient. Additionally, determination of interleukin-5 (IL-5), IL-6, IL-7, tumor necrosis factor-α (TNF-α), and granulocyte-monocyte colony-stimulating factor (GM-CSF) associated with inflammatory processes revealed significantly higher values in prediabetic patients (Lucas et al, 2013). Likewise, cytokines such as interferon-γ (IFN-γ), IL-1β, IL-2, IL-4, IL-8, IL-10, IL12p70, and IL-13 showed an increase in their levels, although not statistically significant.…”
Section: Prediabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…В результате проведенного исследования мы вы-явили крайне низкое содержание IL-10 на фоне повышенных концентраций GM-CSF, IFNγ, IL-6 и TNFα в крови беременных с ГСД и ожире-нием. Схожие результаты были получены и в дру-гих исследованиях при обследовании больных с метаболическим синдромом [3], женщин с из-быточной массой тела и нарушением толерант-ности к глюкозе [11] и больных с ожирением [8]. Дополнительно к описанным выше негативным эффектам цитокинов IL-6 и TNFα следует ука-зать на связь повышенного уровня GM-CSF в крови и активации дендритных клеток с патоло-гическим ремоделированием сосудов и высоким риском развития заболеваний сердечно-сосуди-стой системы у лиц с инсулинорезистентностью и ожирением [14].…”
Section: Discussionunclassified
“…These results confirmed those coming from Rasmussen et al [23] demonstrating no increasing in adhesion molecules VCAM-1 and E-selectin expression on activated endothelial cells in patients suffering from diabetes and pre-diabetes. Nevertheless, Lucas et al [24] recently demonstrated the higher concentrations of serum cytokines [IL-5, IL-6, IL-7, tumor necrosis factor-α (TNF-α), and granulocyte-monocyte colony-stimulating factor (GM-CSF)] in pre-diabetic patients as compared to matched controls. The combination of systemic inflammatory condition and high blood glucose levels is the mixture for the atherosclerosis development: apart from the increase in adhesion molecules concentrations, pre-diabetes and inflammatory condition are associates to plasma asymmetrical dimethyl-l-arginine (ADMA) thus to the development of early endothelial dysfunction in such individuals [25][26][27].…”
Section: Pre-diabetes and Early Impairment In Cardiovascular Systemmentioning
confidence: 99%